Optimizing Supply Chain Management and Stakeholder Collaboration to Increase the Export Potential of Gedong Gincu Mangoes - Dony Susandi; M. Yani Syafei; Herman S. Soegoto (Postgraduate, University of Mataram, 2025)
Gincu Mango as one of the superior varieties of fruit products in Indonesia shows high export potential. Although the export potential is very large, it is inversely proportional to export performance caused by limitations in the supply chain and stakeholder collaboration. This study aims to analyze strategies for improving supply chain management and stakeholder collaboration to increase the export potential of Gedong Gincu mango. This study uses a causal research methodology through the Structural Equation Modeling - Partial Least Squares (SEM-PLS) approach. This method was chosen because of its ability to examine complex relationships between latent variables and its efficiency in handling data with small sample sizes. A survey was conducted to collect data from 100 stakeholders involved in the distribution of Gedong Gincu mango. The results of the study indicate that collaboration between farmers, government agencies, and traders is essential to increasing export activities. One of the key factors found is the importance of accelerating the registration of gardens and packing houses as part of the technical requirements for export, which serve as important technical requirements for export readiness. Furthermore, effective supply chain management shows the capacity to improve coordination and optimize distribution efficiency. However, statistical analysis revealed that the impact of Supply Chain Management on stakeholder collaboration is minimal, although it does affect exports. This study underlines the importance of improving post-harvest infrastructure, educating farmers on export standards, and strengthening strategic partnerships in the supply chain to improve the competitiveness of Gedong Gincu mangoes in the global market